Розробка компонентів інформаційної системи обліку діяльності служби доставки - Дюжев, М. Л. (ХНУРЕ, 2024)
This article briefly examines the activities of a company engaged in the transportation of goods and provides arguments regarding the relevance of this service sector. In addition, the steps that need to be taken to solve one of the main problems of the company, namely document flow, which is kept in paper form, are described. The final solution to this problem is the development of information system components, including a client application, an application server and a database, the overall operation of which provides electronic accounting of the company's activities.
Keywords: служба доставки